2020
DOI: 10.1038/s41438-020-00415-9
|View full text |Cite
|
Sign up to set email alerts
|

CsPrx25, a class III peroxidase in Citrus sinensis, confers resistance to citrus bacterial canker through the maintenance of ROS homeostasis and cell wall lignification

Abstract: Citrus bacterial canker (CBC) results from Xanthomonas citri subsp. citri (Xcc) infection and poses a grave threat to citrus production. Class III peroxidases (CIII Prxs) are key proteins to the environmental adaptation of citrus plants to a range of exogenous pathogens, but the role of CIII Prxs during plant resistance to CBC is poorly defined. Herein, we explored the role of CsPrx25 and its contribution to plant defenses in molecular detail. Based on the expression analysis, CsPrx25 was identified as an apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 76 publications
2
30
0
Order By: Relevance
“…It was also found that the germination rate of prx2prx25 mutant seeds is higher than that of wild-type seeds in Arabidopsis , and mainly because peroxidase affects the polymerization and the level of lignin [ 17 ]. Meanwhile, in Citrus sinensis, the overexpression of CsPrx25 enhanced H 2 O 2 levels and cell wall lignification [ 46 ]. In SN2-RNAi potato, the high lignin level resulted in periderm collapse and was more conducive to tuber sprouting, and CoIP-MS and yeast two-hybrid analysis showed a strong interaction between peroxidases and StSN2, indicating that StSN2 regulated lignin synthesis by interacting with peroxidases ( Figure 6 , Table S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that the germination rate of prx2prx25 mutant seeds is higher than that of wild-type seeds in Arabidopsis , and mainly because peroxidase affects the polymerization and the level of lignin [ 17 ]. Meanwhile, in Citrus sinensis, the overexpression of CsPrx25 enhanced H 2 O 2 levels and cell wall lignification [ 46 ]. In SN2-RNAi potato, the high lignin level resulted in periderm collapse and was more conducive to tuber sprouting, and CoIP-MS and yeast two-hybrid analysis showed a strong interaction between peroxidases and StSN2, indicating that StSN2 regulated lignin synthesis by interacting with peroxidases ( Figure 6 , Table S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the formation of Casparian bands in relation to bacterial action on plants was considered only as a mechanism preventing the entry of pathogenic bacteria into plants [ 21 ]. It was shown that overexpression of class III peroxidase enhanced lignification as an apoplastic barrier for infection [ 22 ]. Nevertheless, the possible promotion of apoplast barrier formation by bacteria as a mechanism of a bacterium-induced increase in salt resistance has never been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…GLU enhances the tolerant of rough lemon rootstock against foot rot (Sandhu et al, 2019), improves the inhibition of rice against Rhizoctonia solani (Kumar et al, 2018), reduces the rice sheath blight (Kaur et al, 2021), and confers tea tree resistance against blister blight disease (Singh et al, 2018). POD is involved in the resistance response of coffee varieties to Colletotrichum kahawae (Diniz et al, 2019), potato to P. infestans , Arabidopsis thaliana to Botrytis cinerea, Colletotrichum higginsianum, and Pectobacterium carotovorum (Zhao et al, 2019), Citrus sinensis to citrus bacterial canker (Li et al, 2020). CAT contributes maize to resistance against maize chlorotic mottle virus infection (Jiao et al, 2021), Nicotiana tabacum against Chilli veinal mottle virus infection (Yang T. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%